Thermal degradation of sulphonylated polystyrene - Coskun, M; Demirelli, K (Elsevier Sci Ltd, 1996)
Three sulphonylated polystyrenes, obtained by sulphonylating polystyrene with the corresponding sulphonyl chlorides, have been characterized by IR and NMR spectroscopy. Elemental analysis shows 76.6, 96.5 and 73.9 mol% of sulphone groups in poly 4-(benzene sulphonyl)styrene, poly 4-(4-toluene sulphonyl)styrene and poly 4-(2-naphthalene sulphonyl)styrene, respectively. Their glass transition temperatures, measured by DSC, are much higher than that of PS. Thermogravimetric studies show that the sulphonylated PSs, with single stage degradation, are similar to PS, but their thermal stabilities are somewhat higher than that of PS. Detailed degradation studies have been carried out only on poly 4-(4-toluene sulphonyl)styrene. Gas chromatography-mass spectrometry (GC-MS) has shown that 4-(4-toluene sulphonyl)styrene is present among the volatile products as 36.3% of the total volatiles. From gas chromatographic studies it has been found that styrene, toluene and SO2 are minor products of the degradation.
Keywords: Keto Polymers; Polymerization